A Selected Bibliography on the International Bank for Reconstruction and Development (The World Bank), 2000-2004 - Kardaras, Basil (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Bibliography on the International Bank for Reconstruction and Development (The World Bank), 2000-2004. This is one of Thirty three selected bibliographies spanning over one hundred pages are presented focusing on scholarship on the Sociology of Development and Women in Development organized by social, political, and economic themes, by global regions (Africa, Asia, Latin America, and the Middle East), and by specialized subjects (for example, globalization, non-governmental organizations, and sustainable development). Additional bibliographies are devoted to journals, internet resources, and videos, along with an annotated bibliography on selected United Nations agencies and organizations